Faktor-Faktor Yang Mempengaruhi Pembelian Produk Blackberry (Studi Terhadap Anggota Milis Telkomsel Blackberry Community Indonesia) - Widya Nur Bhakti Pertiwi (Sains: Jurnal Manajemen dan Bisnis, 2016)
The purpose of this research is to analyze the image of consumers purchase decision making in the conduct of the Blackberry. To find out if a relative advantage, compatibility, complexity, trialabilitas, the ability to communicate the benefits of the product, and observabilitas affect consumer purchasing decisions in the Blackberry product.           The methods used in this research is the author of the research methods of the survey with the quantitative approach. In this research, primary data obtained from the questionnaire. Results of questionnaire data processed using the method of path analysis (path analysis).           Based on the analysis that has been done, the conclusion is relative advantage (X 1), compatibility (X 2), complexity (X 3), trialabilitas (X 4), the ability to communicate the benefits of the products (x 5), and observabilitas (X 6) affect decisions purchase a Blackberry on Blackberry Telkomsel Indonesia Community. Where observabilitas (X 6) that have the greatest contribution in influencing purchase decisions in the respondent's Blackberry product. It is in accordance with the characteristics of high-tech products that are complex, with prices likely to be expensive, need to be examined before being purchased, bought with caution, their life cycle is short, and products that rely on features.